An 8.5 GHz, 0.4 V, 300 ΜW armstrong VCO with dual transformer feedback and capacitor‐splitting gate inductive feedback. Issue 2 (February 2017) - Gul, Muhammad Talha; Ngo, Duc Viet; Nguyen, Xuan Tien; Lee, Jong‐Wook; Park, Hun‐Kuk
ABSTRACT: We present a low‐voltage Armstrong voltage‐controlled oscillator (VCO) suitable for an efficient low‐power wireless connectivity solution. The VCO employing dual transformer feedback in the Armstrong structure is further augmented with low‐power design techniques: the use of a cross‐coupled differential pair, dual transconductance boosting, and capacitor‐splitting gate inductive feedback. The dual transformer feedback and dual transconductance boosting effectively increase the output swing. In addition, the cross‐coupled differential pair is combined with capacitor‐splitting gate inductive feedback, which further reduces the transconductance for startup. The proposed VCO has been fabricated in a 0.18 μm CMOS process; the fabricated device showed successful oscillation at 8.5 GHz while consuming 300 μW at 0.4 V, and its measured phase noise was −104.3 dBc/Hz at a 1‐MHz frequency offset. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 59:384–388, 2017